The effect of structured training in self-disclosure and feedback on self-actualization - Kiok, Dominic Yeo-Koh Tuan, FSG (Animo Repository, 1991)
This project utilized a quasi-experimental design in the study of the effect (immediate, enduring, and delayed) of a structured training program in self-disclosure and feedback on the self-actualization of its participants. The correlation between interpersonal risk-taking and that of self-actualization was also explored. The subjects were 11 undergraduate students (4 males and 7 females) in the experimental group, and 10 undergraduate students (2 males and 8 females) in the control group. The experimental and control subjects were from two classes at the Behavioral Science Department of De La Salle University, Manila. The Personal Orientation Inventory and the Colleague Relations Inventory were used as the dependent standards measuring Self-actualization and Interpersonal risk-taking, respectively. The instruments were administered to all the subjects at the pretest, posttest, and delayed posttest (three weeks after the posttest). The findings of the study, based on the analysis of the Friedman two-way analysis of variance by ranks showed significant changes (at .05 level) from pretest to posttest for the experimental group in the scales of Time competence (Fr = 7.091, df = 2), Self regard (Fr = 7.773, df = 2), and Synergy (Fr = 7.773, df = 2). At the delayed posttest significant changes (at .05 level) were noted from the Friedman test on the scales of Inner-directedness (Fr = 10.955, df = 2), and Capacity for intimate contact (Fr = 6.682, df = 2). No significant correlation was found, at .05 level between Interpersonal risk-taking and self-actualization, except for a slightly significant negative correlation between the minor scales of Capacity for intimate contact and Receptivity to Feedback (rs = -.436). It was observed that the structured training program was effective in promoting self-actualization, that is Time competence, and that of Self-regard and Synergy, immediately following the group experience. The effect did not seem to endure through a three-week wait period. There was delayed effect noted for the major scale of Inner directedness, and the minor scale of Capacity for intimate contact. The correlation between Interpersonal risk-taking and self-actualization could not be established definitely in this study.